PEMBELAJARAN MENGGUNAKAN THINK PAIR AND SHARE MATERI PECAHAN DI SDN 1 LANGADAI - Muhammad Yusuf; Nor Wahdah (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2023)
The aims of research to determine the learning outcomes and student’s responses to learning mathematics fraction material for fifth grade students at SD Negeri 1 Langadai Kotabaru regency, for the 2021/2022 academic year using the Think Pair and Share (TPS) type. To increase student learning activeness, it is necessary to pursue a learning that can involve students in the learning process. One learning model that is able to optimize students’ abilities is cooperative learning. The think pair and share type is a type of cooperative learning that was developed to achieve increased student academic learning outcomes acceptance of diversity and knowledge of social skills. The method used in this research is descriptive method. Data analysis was carried out by tests and questionnaires. The results showed that the learning outcomes of students were in a special qualification after using the cooperative learning model of the think pair and share type on fractional material and students gave responses that strongly agree and agreed. Keywords: Type of Think Pair and Share, Learning Outcomes, Student responses, Fractions